The Nodal signaling pathway controls left-right asymmetric development in amphioxus - Soukup, Vladimir; Yong, Luok Wen; Lu, Tsai-Ming; Huang, Song-Wei; Kozmik, Zbynek; Yu, Jr-Kai (EvoDevo, 2015)
BACKGROUND: Nodal is an important determinant of the left-right (LR) body axis in bilaterians, specifying the right side in protostomes and non-chordate deuterostomes as opposed to the left side in chordates. Amphioxus represents an early-branching chordate group, rendering it especially useful for studying the character states that predate the origin of vertebrates. However, its anatomy, involving offset arrangement of axial structures, marked asymmetry of the oropharyngeal region, and, most notably, a mouth positioned on the left side, contrasts with the symmetric arrangement of the corresponding regions in other chordates. RESULTS: We show that the Nodal signaling pathway acts to specify the LR axis in the cephalochordate amphioxus in a similar way as in vertebrates. At early neurula stages, Nodal switches from initial bilateral to the left-sided expression and subsequently specifies the left embryonic side. Perturbation of Nodal signaling with small chemical inhibitors (SB505124 and SB431542) alters expression of other members of the pathway and of left/right-sided, organ-specific genes. Upon inhibition, larvae display loss of the innate alternation of both somites and axons of peripheral nerves and loss of left-sided pharyngeal structures, such as the mouth, the preoral pit, and the duct of the club-shaped gland. Concomitantly, the left side displays ectopic expression of otherwise right-sided genes, and the larvae exhibit bilaterally symmetrical morphology, with duplicated endostyle and club-shaped gland structures. CONCLUSIONS: We demonstrate that Nodal signaling is necessary for establishing the LR embryonic axis and for developing profound asymmetry in amphioxus. Our data suggest that initial symmetry breaking in amphioxus and propagation of the pathway on the left side correspond with the situation in vertebrates. However, the organs that become targets of the pathway differ between amphioxus and vertebrates, which may explain the pronounced asymmetry of its oropharyngeal and axial structures and the left-sided position of the mouth.
Keywords: Nodal signaling; Mouth opening; Embryonic development; Amphioxus; Left-right asymmetry